A safe haven for everyone: Working with shared values in a nursing home for people with dementia. (September 2019) - Söderlund, Mona; Fagerberg, Ingegerd
The aim of this study was to describe from a staff perspective what promotes a positive atmosphere in a nursing home for people with dementia. A nursing home renowned for its positive atmosphere and quality of care was chosen for our research. The study has a qualitative descriptive design using a modified grounded theory. Eight members of staff were interviewed. The analysis consisted of open, axial and selective coding and constant comparison between each narrative. The core category was 'A safe haven for everyone', with three categories; 'Relating to people with dementia', 'Relating to work' and 'Relating to each other'. A shared set of values embraced by all staff was the foundation in the nursing home and supported the atmosphere and quality of care. The positive atmosphere had been founded on mutual trust between manager and staff, lending staff the freedom to be creative in their work, and ensuring that the residents with dementia were cared for in the best possible way.